2009
DOI: 10.1159/000209331
|View full text |Cite
|
Sign up to set email alerts
|

Fourteen-Year Prospective Follow-Up Study of Positive and Negative Symptoms in Chronic Schizophrenic Patients Dying from Suicide Compared to Other Causes of Death

Abstract: Background: Several trials have suggested that negative symptoms are inversely correlated with suicidal risk in schizophrenic patients. This fourteen-year follow-up study compared the positive and negative symptoms of schizophrenic patients who died from suicide to those of subjects dying from other causes. Sampling and Methods: From 1991 to 1995, 150 patients meeting the research diagnostic criteria for chronic schizophrenia were assessed. On inclusion, they completed the Physical Anhedonia Scale as well as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 33 publications
2
23
0
Order By: Relevance
“…Anhedonia is an important behavior to study because, in humans, the presence of anhedonic symptoms in a setting of depression is predictive of suicidal thoughts and behaviors [2630]. Our amygdala-dependent anhedonia model is, therefore, consistent with human studies, in which numerous gene and protein expression studies have demonstrated a relationship between the physiologic state of the amygdala and the occurrence of a successful suicide.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Anhedonia is an important behavior to study because, in humans, the presence of anhedonic symptoms in a setting of depression is predictive of suicidal thoughts and behaviors [2630]. Our amygdala-dependent anhedonia model is, therefore, consistent with human studies, in which numerous gene and protein expression studies have demonstrated a relationship between the physiologic state of the amygdala and the occurrence of a successful suicide.…”
Section: Discussionsupporting
confidence: 72%
“…While depression is a complex disorder with multiple symptoms, we have chosen to focus on the anhedonic symptom of depression because it is a key symptom of depression that is highly predictive of suicidal thoughts and behaviors [2630] and is common in patients with MTLE [31,32]. The model we are introducing is produced by inhibiting glutamine synthetase, an astrocytic enzyme that is critical for the metabolism of glutamate and ammonia to glutamine, in the central nucleus of the amygdala (CeA).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has identified a relationship between suicidal ideation and anhedonia; however, the extant literature has provided mixed results regarding the relationship between anhedonia and suicide. For instance, some research suggests that low levels of anhedonia may be characteristic of those dying by suicide (Loas, 2007;Watson & Kucala, 1978), whereas other research suggests high levels of anhedonia as one of several predictors of fatal suicide attempts (Fawcett, Clark, & Busch, 1993;Fawcett et al, 1990;Hall, Platt, & Hall, 1999;Loas, Azi, Noisette, Legrand, & Yon, 2009). In the current studies, we found that anhedonia was associated with suicidality but not related to previous suicide attempts.…”
Section: Discussionmentioning
confidence: 99%
“…3 Research has shown that deficit patients, as compared with nondeficit patients, have poorer premorbid functioning, 4 more severe neurocognitive impairment, 5 worse functional outcome, 6 and substantially lower rates of remission and recovery. 7 Yet, despite a worse prognosis, deficit patients experience less overall negative affect, 8 have a lower risk for suicide, 9 and abuse substances less than nondeficit patients. 10 Whereas neurobiological research has identified anomalies associated with the deficit syndrome in the areas of eye tracking, 11 olfaction, 12 event-related potentials, 13 and neuroanatomy, 14 these findings have not translated into improved treatments.…”
Section: Introductionmentioning
confidence: 99%